ARTSTEP VIRTUAL EXHIBITION: SOLUSI KREATIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Munir, Zahra Alfirdausy; MS Khabibur Rahman; Universitas Veteran Bangun Nusantara Sukoharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology offers new opportunities to improve the quality of learning in elementary schools, so teachers must be able to utilize technology to support learning activities. There are several technology-based media that teachers can use, one of which is the ArtStep Virtual Exhibition. This study aims to find out the effectiveness of the ArtStep Virtual Exhibition digital media in improving students' motivation and academic achievement in the Pancasila Education subject. The research methodology used is Classroom Action Research (CAR), which consists of two cycles. The analysis results showed a significant increase from cycle 1 to cycle 2. In cycle 1, the average student score was 58.57, most of whom were in the "Very Poor" and "Poor" classifications. After the implementation of the ArtStep Virtual Exhibition media, the average score increased to 77.14 in cycle 2, with the majority of students (60.71%) classified in the "Very Good" category, thus eliminating students in the "Very Poor" category. ArtStep media, which dynamically combines visual, auditory, and textual components, has successfully fostered a conducive learning environment, increased motivation, and encouraged the development of character and national values. This study recommends using digital interactive media as one of the options in Pancasila Education to improve learning outcomes more effectively.